VALIDITY OF ELECTRONIC MODULE BASED ON TUTORIAL VIDEOS AUTOCAD 3 DIMENSION - Kurniawan, E D; Nopriyanti, Nopriyanti; Sucipto, S D (Sriwijaya University Learning and Education International Conference, 2018)
This study aimed to produce electronic module based on a valid tutorial videos. Electronic module based on tutorial videos discuss AutoCAD 3 dimension. This study used Research and Development (RnD) method with 4D (Define, Design, Develop, and Disseminate) model. The study involved students from mechanical engineering Education of Sriwijaya University that enrolled in CAD/CAM course. The results of this study showed that the developed module was valid. This was shown by the assessment from expert of material with very good score as well as the assessment from expert of media with a good score.